The housing delivery system in Rangoon, Burma - Chit, Myitzu; Angel, Shlomo; Kammeier, Hans Detlef; Kaji, Hideki; The Canadian International Development Agency (Bangkok : Asian Institute of Technology, 1981)
This paper consists of a. brief review of housing, urbanization and physical planning in Ran goon. The political, organizational, financial and physical dimensions were studied. An attempt was made to identify the possible situations where improvement in housing conditions and the provision o f basic amenities and services could be achieved through using the limited development resources o f the Socialist Republic of the Union of Burma. According to the analysis found, the new housing schemes are unable to solve the majority of the people's housing problems. Also, relocation should be the lowest priority f or the slum people. The nest way would be to use all the existing available resources effectively by upgrading the system. When the country has limited resources, improvement programmes have to be carried out instead of wasting the existing resources. Professionals should consider the point and the government also should not leave the peoples housing problem as it is, but should take action soon .
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Science
Thesis (M.Sc.) - Asian Institute of Technology, 1981
Keywords: Housing research -- Burma -- Rangoon